2012
DOI: 10.1016/j.jjcc.2012.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma brain natriuretic peptide levels predict left atrial appendage dysfunction in patients with acute ischemic stroke

Abstract: Elevated plasma BNP concentrations may be a reliable surrogate marker for the prediction of LAA dysfunction and cardiogenic stroke in patients with acute ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 30 publications
1
17
1
Order By: Relevance
“…In a previous study by Tamura et al, the association between BNP and LAA function in patients with acute ischemic stroke was reported. 24 They showed that plasma BNP levels significantly correlated with LAAFV regardless of SR or AF rhythm, which was similar to the result in our study. BNP is secreted into the plasma mainly in response to mechanical stretching of the LV, LA and LAA myocardium.…”
Section: Patient Populationsupporting
confidence: 91%
“…In a previous study by Tamura et al, the association between BNP and LAA function in patients with acute ischemic stroke was reported. 24 They showed that plasma BNP levels significantly correlated with LAAFV regardless of SR or AF rhythm, which was similar to the result in our study. BNP is secreted into the plasma mainly in response to mechanical stretching of the LV, LA and LAA myocardium.…”
Section: Patient Populationsupporting
confidence: 91%
“…The peak early (E') mitral annular velocity was measured, and the ratio of the E-wave to E' (E/E') was calculated, as previously described. 13 All echocardiographic measurements were calculated as the mean of 5 consecutive cardiac cycles. 14 LAA thrombus was diagnosed when a fixed or mobile echogenic mass could be clearly differentiated from the wall of the LA or LAA.…”
Section: Echocardiographymentioning
confidence: 99%
“…14 LAA thrombus was diagnosed when a fixed or mobile echogenic mass could be clearly differentiated from the wall of the LA or LAA. 13 The severity of spontaneous echocardiographic contrast (SEC) was graded from 0 to 4+ by 2 independent observers who were unaware of the blood data: 0=none; 1+=mild; 2+=mild to moderate; 3+=moderate; and 4+=severe. 15…”
Section: Echocardiographymentioning
confidence: 99%
“…39 Therefore, it is believed that in a patient with AF, BNP is primarily produced in the atria, whereas in a patient with heart failure, natriuretic peptide is mainly released by ventricles. 40,41 Elevated levels of BNP have been correlated with left atrial appendage dysfunction, 42,43 which itself is associated with increased risk for thromboembolic events in AF patients. 14 The prevalence of elevated biomarkers and their association with cardiovascular events in AF patients receiving chronic anticoagulation were studied independently in two clinical trials: Apixaban for the Prevention of Stroke in Subjects with Atrial Fibrillation (ARISTOTLE) and Randomized Evaluation of Long-Term Anticoagulation Therapy (RE-LY).…”
Section: Brain Natriuretic Peptidementioning
confidence: 99%